Image_12.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The flattened dough is then cooked on a tava heated from underneath. Koli women typically use a cast-iron tava for this purpose. The bhakri is cooked on both sides until it is golden brown, being flipped multiple times during this process to ensure that it is cooked evenly.